Abduction by Philosophers: Reorienting Philosophical Methodology. (July 2016) - Andow, James
Abstract: A reorientation is needed in methodological debate about the role of intuitions in philosophy. Methodological debate has lost sight of the reason why it makes sense to focus on questions about intuitions when thinking about the methods or epistemology of philosophy. The problem is an approach to methodology that focuses almost exclusively on questions about some evidential role that intuitions may or may not play in philosophers' arguments. A new approach is needed. Approaching methodological questions about the role of intuitions in philosophy with an abductive model of philosophical inquiry in mind will help ensure the debate doesn't lose sight of what motivates the debate.